Strategi Bimbingan Ustadzah Dalam Meningkatkan Kemampuan Bahasa Madura Halus Pada Santri Putri Pondok Pesantren Hidayatul Ulum Waru Timur Pamekasan - Fajriyah, Lailatul; Rofiki, Rofiki; Baidowi, Ach. (Al Irsyad: Jurnal Studi Islam, 2022)
The purpose of the study was to describe the ustadzah's guidance strategy in improving the fine Madura language skills of students, supporting and inhibiting factors, and the impact of these strategies on students' English skills. The research method used is qualitative research with a case study approach—observation, interviews, and documentation collected data. The results of the study revealed that: 1) The implementation of the smooth Madurese language learning process using the Lecture, Memorizing, and Nyayian method at the Hidayatul Ulum Islamic Boarding School. The form of the smooth Madurese language learning activities with this method, among others: a. Memorization deposit to ustadzah; b. Learn to memorize by singing fine Madurese vocabulary. c. Listen carefully to what the cleric says when the lecture method is carried out. 2) Supporting factors in learning the acceptable Madurese language at Islamic Boarding Schools include: routine guidance activities, ustadzah expertise in teaching, and takziran or punishment for students who violate the rules. The inhibiting factors for learning the acceptable Madurese language at Hidayatul Ulum Islamic Boarding School include: a lack of student interest in learning, a lack of a student mentality, and differences in student character. 3) The impact of this learning is considered effective because the results seen in students are good. This can be seen from the results of tests and trials conducted by participants.